“El principio de concentración y su incidencia en los tramites de disolución de la sociedad conyugal en la unidad judicial de la familia mujer niñez y adolescencia del cantón Riobamba, de enero a julio del año 2016.” - Lozada Quisnancela, Francis Javier (2017)
The present investigation will be based on the study of the principle of concentration, we will identify if it is applied correctly in the proceedings and hearings by the judges, through the oral trial where it is applied, since hardly a written procedure allows the Concentration of actions, since it is necessary to wait for the presentation of a brief to prepare, after careful consideration, the adequate written reply, within a period, and so on, in this way we will corroborate that there is no breach of constitutional principles, We will also see that other principles have correlation with the principle of concentration. The principle of concentration will apply mainly to the process to dissolve the conjugal partnership, both in the judicial process and in the notarial process. The research is also focused on the legal figure of the conjugal society, we will see that the conjugal society is an effect of marriage and as it applies the dissolution within all types of assets that may exist in it, we will analyze legal gaps within the dissolution Conjugal, and through concepts we will differentiate it from the conjugal liquidation, in this way we will identify the causes that give effect to the conjugal dissolution, the types of procedures and in each one of them we will see how the principle of concentration applies.